Understanding Exercise Motivation in the Tâmega and Sousa Region: A Gender-Based Analysis - João Pedro Pinto; Alexandra Malheiro; Alberto Rocha; José Teixeira; Nelson Valente; Bekir Erhan Orhan; Joana Ribeiro; Pedro Afonso; Javier Murillo-Moraño; Juan de Dios Benítez Sillero; Pedro Forte; Luís Branquinho (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2025)
The purpose of the study. To assess gender differences in motivations for physical exercise among adults in the Tâmega and Sousa region of Portugal, testing the hypothesis that men and women differ in their exercise motivations. Materials and methods. An observational, descriptive, and inferential study was conducted between February and May 2024 using the Exercise Motivations Inventory-2 (EMI-2), a validated 51-item questionnaire across 14 subscales. Data were collected electronically via Google Forms and disseminated through social media platforms (Facebook, Instagram, LinkedIn, WhatsApp) and email. The sample comprised 100 participants (24 men, 76 women) with mean ages of 32.00 ± 13.31 years for men and 32.88 ± 10.33 years for women. Statistical analysis included descriptive statistics, Kolmogorov-Smirnov normality tests, independent samples t-tests, and Cohen's d effect size calculations using SPSS version 24.0. Results. Statistically significant gender differences were found in individual exercise motivations (p ≤ 0.05). Women demonstrated significantly higher motivation for preventing health issues, improving endurance, managing stress, avoiding illness, improving agility, weight management, engaging in social activities, and relieving tension compared to men. Men showed greater motivation for competition and achieving unique personal goals. However, no significant differences were observed between genders in the overall EMI-2 subscales. Conclusions. The study confirmed the hypothesis that men and women have different motivations for physical exercise, with women more motivated by health-related and stress management factors, while men prioritize competition and personal achievement. These findings suggest the need for gender-specific strategies in promoting physical activity. Limitations include convenience sampling, small sample size, gender imbalance, and lack of consideration for physical activity levels and exercise barriers. Future research should employ larger, more representative samples and incorporate additional variables for comprehensive analysis to inform targeted health promotion interventions.